Relating structural test and FEA data with STEP AP209. (January 2019) - Lanza, R.; Haenisch, J.; Bengtsson, K.; Rølvåg, T.
Highlights: Structural test and analysis data in one consistent data model. Using ISO 10303 STEP AP209 to keep the traceability between structural testing and analysis. Improving data retention of structural test and simulation data using STEP. Abstract: This paper proposes a method for incorporating FEA data and structural test data into one common standardized data model based on the ISO 10303 STEP Standard[1] . The proposed method takes advantage of data structures and elements defined in STEP AP209 Edition 2[2] to provide traceability between analysis and testing phases; information such as sensor and finite elements, test and FEA load cases, and test and FEA results are included. It also presents an introduction to STEP and AP209e2, and discusses how it can be used in a Simulation Data Management environment.